THE EFFECT OF INOSITOL, PYRIDOXINE AND THIAMINE ON SOMATIC EMBRYOGENESIS OF Agave angustifolia - J. I. Reyes-Díaz; A. M. Arzate-Fernández; J. L. Piña-Escutia; T. H. Norman-Mondragón (Tropical and Subtropical Agroecosystems, 2020)
Background: Somatic embryogenesis in Agave angustifolia is an option for massive in vitro propagation and genetic improvement of this species, this process involves the induction of embryogenic callus, the development and maturation of embryos and their germination to form a complete plant. In this sense, an optimized selection of the compounds of the culture medium is required. Objective: This study evaluated the effect of vitamin components (inositol, pyridoxine and thiamine) on callus formation and induction of somatic embryos in A. angustifolia. Methodology: Two consecutive assays were conducted, assay I consisted of eight treatments to determine the isolated effect and in combination of three vitamin compounds (250.0 mg of L-1 inositol, 0.5 mg of L-1 pyridoxine and 2.0 mg of L-1 thiamine). In assay II the effect of six concentrations of thiamine (1.5, 2.0, 2.5, 3.0, 3.5 and 4.0 mg L-1) was determined. In both assays, a completely randomized experimental design was used and each treatment had 20 repetitions. Results: The results of assay I show that the formulation of the vitamin complex of the culture medium plays a fundamental role in this process, suggesting that thiamine is an essential compound for the induction of somatic embryos (SE) of A. angustifolia because calluses obtained in thiamine supplemented media (alone or in combination) had a better embryogenic response than those not supplemented with this compound; In addition, in assay II with the increase in the concentration of thiamine to 2.5 and 3.0 mg L-1 in the culture medium, it is possible to induce a higher number of SE per explant (50.5 and 55.9, respectively), compared to 35.8 SE induced with the original concentration of thiamine (2.0 mg L-1). Implications: The results of this study contribute to a better understanding of the importance of the formulation of the vitamin complex and the effect of its addition in the culture medium to induce a greater number of SE in A. angustifolia. This can help in the beginning of programs of genetic improvement and ex situ conservation of this species. Conclusion: The results of this research suggest that thiamine is an essential compound for the acquisition of embryogenic potential in the somatic cells of A. angustifolia, since by increasing the concentration of this component in the culture medium it is possible to obtain a greater number of somatic embryos with high ex vitro survival rates.